The Analysis and Critique of Amartya Sen's Approach to Development - Seyyed Aqil Hoseiny; Seyyed Esmaeil Masoudi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی, 2018)
The main hypothesis of Amartya Sen in his famous book "Development as Freedom" is that the private freedom should be recognized for overcoming the problem of development. According to Sen's liberal approach, the freedom is both the tool and the end of development. Essentially development is the process of extending the actual freedoms such as increasing longevity and life expectancy and in fact the increasing of the quality of life.Several criticisms have been leveled against this approach, for example the inconsistency between the essential characters of Sen's approach to development such as the instrumental rationality and freedom. Also, the Sen's claims that there are positive relationship between democracy and development, and the negative relationship between population and development are doubtful and has been criticized. Since the Sen's approach has no predetermined and essential deontological requirement except freedom itself, itis inconsistent with the deontological systems such as religion. Finally, the historical and structural relationship between individual and nations have not been seriously taken into account.